Comprehension of experienced English language teachers' professional identity and related metacognitive thinking procedures. Issue 1 (19th May 2021) - Han, Insuk
ABSTRACT: In order to comprehend the attributes of expert teachers, the current study investigated professional identity (PI) and related metacognitive thinking procedures of experienced Korean teachers of English through a questionnaire survey and interviews. The teachers' PIs contained pedagogic meanings that highly regarded teachers' having language knowledge and skills, realising learner-centred practices, teaching communication skills for practicality, and developing professionalism. They relatively less valued practising teacher-led, test-preparation lessons but also using challenging tasks and creative materials and combining content, materials, and activities, which reflects their unestablished meanings of learner-centredness. Some of the interviewed teachers revealed their active performance of metacognitive monitoring and regulations of different meanings (cognitions), emotions, and actions over their pedagogical problem-solving processes for overcoming teacher-led, test-preparation lessons. Thus, experimenting with negotiated pedagogies and modifying their pedagogic meanings by learning from this, they tried to balance identity-congruent actions and verification, and reshaped their PI and related metacognitive thinking procedures; others' pedagogic experimentations and related experiences were rejected by contextual rigidities. Comprehension of the PI and related metacognitive thinking procedures of experienced teachers provided several implications for teacher education.